Endodontic Re-Treatment of Maxillary Second Molar with Two Separate Palatal Roots: A Case Report - Ghoddusi, Jamileh; Mesgarani, Abbas; Gharagozloo, Salman (Iranian Endodontic Journal, 2008)
Maxillary second molar with two palatal roots is a rare dental anatomy. The diagnosis and treatment of exceeded root may create challenge for clinicians. The authors discuss the retreatment of a maxillary second molar in which exceeded root was undiagnosed in previous treatment. The case report underlines the importance of complete knowledge about root canal morphology which achieved by careful clinical and radiographic examination. In retreatment procedures clinicians should consider missed canals.